Comparação de diferentes sistemas de produção de gado de corte visando a carne de qualidade - Ivo, Pedro Felipe Di Madureira (Universidade Federal de São Carlos, 2021)
The rural producer of bovine animal protein, in supplying their production, does not have enough scale or market organization to define and/or influence better prices compared to the price offered in the agro-industrial market by buyer increasingly concentrated. Inserted in a market in perfect competition, the homogeneous product adds a characteristic that leads the producer rural to have a profit margin that tends to zero. Still, productive practices of the conventional producer are impregnated with elements that fight the competitiveness of its activity and its long-term viability, as the market has repositioned with new admissibility criteria for rural production. For another On the other hand, the product offered by the producer finds, at the end of the chain, a value exponentially higher than the remuneration achieved by the rural producer. How the transfer of proteins takes place in the productive chain of consumption agroindustrial, there is greater selectivity and greater remuneration for the product. The goal of this work was to evaluate elements that add viability characteristics to the livestock activity to capture value within the animal protein production-processing consumption chain. Through the case study it was found that the genetic characteristics of the herd; the development of integrated activities of use of the soil; the reduction of the production cycle; the animal nutrition system and, finally, the marketing structure are elements that lead to the viability of production livestock.
Comparison of different beef cattle production systems aiming quality meat
Keywords: Pecuária; Cultura bovina; Carne de qualidade; Sistemas de produção; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL